2021
DOI: 10.1016/j.cej.2020.127778
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the estimation of the Sanchez-Lacombe interaction parameters for the solubility of ternary polyolefins systems

Abstract: The total solubility of ethylene in LLDPE in presence of propane, isobutane and 1-butene is measured using a gravimetric technique at 70°C and pressures up to 5 bars. In order to overcome the lack of experimental partial solubility data in ternary systems, a novel approach for the estimation of the Sanchez-Lacombe interaction parameters is proposed. The total solubility measurements combined with the independent estimate of the compressibility factor 2 for a mixture of gases using Peng-Robinson EoS as a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…There is thus a higher deviation of the interaction between the polymer and 1-butene, than propylene, than propane. This was also observed for the ternary experiments performed on the magnetic suspension balance . Furthermore, Bashir et al noted that unlike ethylene, propylene, and hexene at 90 °C, only 1-butene showed a negative k ij in a binary system.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…There is thus a higher deviation of the interaction between the polymer and 1-butene, than propylene, than propane. This was also observed for the ternary experiments performed on the magnetic suspension balance . Furthermore, Bashir et al noted that unlike ethylene, propylene, and hexene at 90 °C, only 1-butene showed a negative k ij in a binary system.…”
Section: Resultssupporting
confidence: 57%
“…The novel approach used in our previous work in which the SL EoS is combined to the Peng–Robinson EoS (i.e., PR EoS) cannot be used for quaternary systems when only overall solubility data are available because three interaction parameters cannot be identified from only two input data. This makes the pressure decay method, from which partial solubilities are measured, crucial to model the solubility of quaternary systems with SL EoS.…”
Section: Modelingquaternary Sl Eosmentioning
confidence: 99%
“…Sorption experiments with a MSB can be used to measure both the equilibrium solubility and the overall diffusivity of a gas (or mixture of gases [5,6,11,12] ). A typical sorption curve is shown in Figure 1.…”
Section: Estimation Of Diffusion Coefficientsmentioning
confidence: 99%
“…[2][3][4] However, one significant point that emerges from a perusal of the references in the review articles just cited is that there is a significant lack of data concerning both solubility and diffusivity of multicomponent gas phase mixtures. [5][6][7][8] This information is crucial, particularly in terms of understanding mass transfer and the evolution of the concentrations of reactive species in the growing polymer particles under realistic polymerization conditions. Typical polymerization recipes contain not only ethylene, hydrogen, and nitrogen, but DOI: 10.1002/macp.202100406 also co-monomers and inert alkanes that help to improve the control of the reactor temperature by increasing the heat capacity of the gas phase, and, when liquefied, through the latent heat of evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary data of this system is available at 70 °C within a total pressure of the monomer plus comonomer in the range of 2.5−4 bar, for which the interaction parameters k ij were identified (Table 2). 37 It is required to extrapolate these parameters to 90 °C and to a wider range of pressure. For this extension, few assumptions were made, but the estimations can be improved once ternary data becomes available at 90 °C and under the real operating pressure.…”
Section: ■ Introductionmentioning
confidence: 99%